The fire below how the Caucasus shaped Russia - Ware, Robert Bruce (Bloomsbury Academic, 2013)
This book will be vital to those who are interested not only in politics and the dynamics of Russia, but in Olympic sports as well. After reading this volume Russia, the Caucasus, and even the Olympics will never seem quite the same again.